2009
DOI: 10.1007/s00442-009-1482-y
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term influence of environment on recruitment in a species with highly delayed maturity

Abstract: Short-term effects of environmental perturbations on various life history traits are reasonably well documented in birds and mammals. But, in the present context of global climate change, there is a need to consider potential long-term effects of natal conditions to better understand and predict the consequences of these changes on population dynamics. The environmental conditions affecting offspring during their early development may determine their lifetime reproductive performance, and therefore the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…Due to extended pre-breeding period (sometimes longer than 10 years in seabirds; e.g., Jenouvrier et al 2008) and 'insufficient' duration of research projects (relative to the mean longevity in the studied species), most studies have focused on the following traits: post-fledging juvenile survival, survival from independence to recruitment, or recruitment probability (Hario and Rintala 2009;Meathrel and Carey 2007). Longer term consequences of conditions during development have rarely been addressed (Nevoux et al 2010). Naturally, a large number of studies of short-lived birds have also focused on pre-breeding survival and age of first breeding (e.g., LindĂ©n et al 1992;Magrath 1991;Verboven and Visser 1998).…”
Section: Specific Methodological Challengesmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to extended pre-breeding period (sometimes longer than 10 years in seabirds; e.g., Jenouvrier et al 2008) and 'insufficient' duration of research projects (relative to the mean longevity in the studied species), most studies have focused on the following traits: post-fledging juvenile survival, survival from independence to recruitment, or recruitment probability (Hario and Rintala 2009;Meathrel and Carey 2007). Longer term consequences of conditions during development have rarely been addressed (Nevoux et al 2010). Naturally, a large number of studies of short-lived birds have also focused on pre-breeding survival and age of first breeding (e.g., LindĂ©n et al 1992;Magrath 1991;Verboven and Visser 1998).…”
Section: Specific Methodological Challengesmentioning
confidence: 98%
“…Depending on the fitness component considered, studies of long-term fitness consequences of early conditions in different species have provided some indication that fitness consequences are either not perceptible before recruitment (post-fledging survival and recruitment probability; Hipfner 1999; Drummond et al 2003), not detectable after recruitment, or no longer detectable after recruitment even if earlier fitness consequences might have been detected (Nevoux et al 2010). Alternatively, van de Pol et al (2006a) found evidence of long-term consequences of the quality of the habitat experienced during growth in Oytercatchers on both survival probability and reproductive success, through the quality of the habitat in which they recruit.…”
Section: Long-lived Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the analysis of capturemark-encounter data have provided a robust framework for estimation of and analysis of variation in recruitment while controlling for possible differences in encounter probability and imperfect detection of breeding individuals (Clobert et al 1994 Crespin et al 2006;Jenouvrier et al 2008;Nevoux et al 2010; see Lebreton et al 2009 for a recent review). Recent work by Cam et al (2005) considered the influence of assumptions concerning equivalence of survival probability of pre-breeders and breeders if pre-breeders are unobservable (Clobert et al 1994;Pradel and Lebreton 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We used an estimate of juvenile survival probability from Nevoux et al [41] assuming that juvenile survival (Sj) was constant over the first 5 years (Sj 0 -5 ÂŒ Sj 0 -1 *Sj 1 -2 *Sj 2 -3 *Sj 3 -4 *Sj 4 -5 ÂŒ 0.281). There was no data to estimate annual variation of juvenile survival before recruitment because young birds stay at sea permanently from fledging until first return on land.…”
Section: (C) Population Modelmentioning
confidence: 99%